146k views
1 vote
6th grade question please help show work

6th grade question please help show work-example-1
User Gamal A
by
5.2k points

1 Answer

0 votes

Answer:

A. -6

Explanation:

Simplify the given expression.

(6x^4 - 3x^2) + (x^2 - 5)(qx^2 + 5) =

= 6x^4 - 3x^2 + qx^4 + 5x^2 - 5qx^2 - 25

= 6x^4 + qx^4 + 2x^2 - 5qx^2 - 25

= (6 + q)x^4 + (2 - 5q)x^2 - 25

Set ti equal to the given solution.

(6 + q)x^4 + (2 - 5q)x^2 - 25 = 32x^2 - 25

The solution has no 4th degree term, so

6 + q = 0

q = -6

As a check, the solution's x^2 term is 32x^2, so

(2 - 5q)x^2 = 32x^2

2 - 5q = 32

-5q = 30

q = -6

Once again, we get q = -6.

Answer: A. -6

User Roshan S
by
5.9k points